Solution for Processing Pelvic Bone Metastases with Halcyon TM 2.0 on Lateral and Longitudinal Isocenters Treatment Plans Using the VMAT Technique: A Comparative Study - Morad Erraoudi; Kaoutar El Bouchiti; Yassine Herrassi; mohamed El ghalmi; Yassir Raoui; Youssef Bouzekraoui; FARIDA BENTAYEB; Lalla Btissam Drissi (Iranian Journal of Medical Physics)
Introduction: Treatment of pelvic bone metastases using a Halcyon machine, mostly presents some difficulties to plan, especially for big volumes because of the machine field size. The purpose of this study is to use two lateral isocenters in the treatment of pelvic bone metastases with the Halcyon machine, in order to overcome its limitations in treating large volumes.Material and Methods: We report a retrospective study of 8 patients who received radiotherapy for pelvic bone metastases, all treated by two different VMAT techniques. The first technique was performed by two longitudinal isocenters (LONI) and the second by two lateral isocenters (LATI) respecting the authorized distance longitudinally between two isocenters which must be less than 8 cm. For each isocenter, two opposite arcs are used for all treated patients.Results: The plans conformity index (CI) assessment shows no difference between the two used techniques for all the treated patients. Remarkable coverage of PTVs was obtained in lateral isocenter (LATI) with 96.2% compared to 94%.6% for LONI, as well as the maximum dose which was 109.4% for LATI versus 112.3% for LONI. However, the Conformation number (CN) that takes into account both healthy tissue and organ at risk protection was improved by 7.3% by using LATI.Conclusion: A very satisfactory result has been obtained in the treatment of pelvic bone metastases with LATI. With this technique, we can exceed the limits of the Halcyon machine and process larger volumes.